Training on Developing Interactive Learning Media Applications Using Microsoft PowerPoint for Members of the IV Demlat Regiment, Mobile Brigade Corps (Brimob), Indonesian National Police, Kelapa Dua Cimanggis, Depok - Amalia, Rini; Sagita, Sri Melati; Faisal, Ahmad (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
This community service activity aims to improve instructors’ ability to develop interactive learning media using Microsoft PowerPoint for members of the IV Demlat Regiment of the Mobile Brigade Corps (Brimob) of the Indonesian National Police in Kelapa Dua, Cimanggis, Depok. The background of this activity is the limited use of interactive learning media, where the training process tends to rely on lecture methods and books as the main sources, making it less engaging and less effective. The implementation method used was a workshop with a hands-on practice approach, including the delivery of basic materials, demonstrations, and mentoring in developing interactive learning applications. Participants consisted of staff from the Testing and Development Unit (Ujibang) and the Instructor Coordinator Unit (Korins). The results showed that participants were highly enthusiastic in attending the training and began to be able to develop PowerPoint-based learning media, although some participants still had limitations in basic computer skills. Overall, this training succeeded in improving instructors’ understanding and skills in presenting more engaging and interactive learning materials, which is expected to enhance the quality of the training process within Brimob.